FLORAE MALESIANAE PRAECURSORES XV*THE GENUS GAULTHERIA IN MALAYSIA - H. SLEUMER (BRIN Publishing (Penerbit BRIN), 1957)
In this revision of the Malaysian species of the genus Gaultheria Kalm ex L. 24 species and 9 varieties resp. forms are recognized. Among the new taxa described are 9 species and 1 variety. The localities of the revised material are given in detail. An index to specimens is added.